A Virtual Network Mapping Algorithm Based on Approaching Principle - Sheng Huang; Chuanchuan Wu; Xiaofei Yang; Hui Wang; Wei Zhang (Dianxin kexue)
On the basis of two stages virtual network mapping algorithm, pointing at the defects of the blind node mapping of existing greedy strategy, a virtual network mapping algorithm based on approaching principle was proposed. The algorithm optimized and improved the node mapping stage, and it took a full consideration of the impact on link mapping in the node mapping stage, which made the nodes map to the area of relatively concentrated and reduced the difficulty of solving the link mapping stage. Simulation results show that compared with the existing algorithms, the proposed algorithm improves the virtual network request acceptance ratio, average time revenue and revenue/cost（r/c）ratio.